The PENGARUH TEKNIK PERNAPASAN BUTEYKO TERHADAP KEKAMBUHAN ASMA BRONKIAL - Maskhanah Maskhanah; Noorhidayah Noorhidayah; Rivan Firdaus (MNJ (Mahakam Nursing Journal), 2019)
Bronchial asthma is a disease that can not be cured so that proper prevention is necessary, one of them with Buteyko breathing techniques that can reduce hyperventilation. The purpose of this study to analyze the effect of Buteyko breathing techniques on bronchial asthma relapse. research design using Quasi Experiment pre and post test without control. The population amounted to 349 outpatient asthma patients Lempake Puskesmas. The sample size is 8 people with the formula Roscoe (1975) and Arikunto (2010) = 11 respondents with drop out 3 respondents and using consecutive sampling technique. The instrument used an observation sheet of asthma symptoms adopted from the mardhiah study (2009). The study time is 3 times a day for 2 weeks. From result of analysis obtained p value at pretest 0,002; Post test1 0,018 and post test2 0.002. All three scores <0.05 (95% confidence) then H0 rejected so that Ha accepted Buteyko breathing techniques can reduce the recurrence of asthma. Suggestion researchers, for further research is expected to compare Buteyko breathing techniques with other methods in terms of asthma relapse. Keywords: Bronchial asthma, Buteyko breathing technique, asthma symptoms.